The Promise and Pitfalls of Environmental DNA and RNA Approaches for the Monitoring of Human and Animal Pathogens from Aquatic Sources. (21st April 2021) - Farrell, Jessica A; Whitmore, Liam; Duffy, David J
Abstract: Novel forensics-inspired molecular approaches have revolutionized species detection in the wild and are particularly useful for tracing endangered or invasive species. These new environmental DNA or RNA (eDNA or eRNA)–based techniques are now being applied to human and animal pathogen surveillance, particularly in aquatic environments. They allow better disease monitoring (presence or absence and geographical spread) and understanding of pathogen occurrence and transmission, benefitting species conservation and, more recently, our understanding of the COVID-19 global human pandemic. In the present article, we summarize the benefits of eDNA-based monitoring, highlighted by two case studies: The first is a fibropapillomatosis tumor-associated herpesvirus (chelonid herpesvirus 5) driving a sea turtle panzootic, and the second relates to eRNA-based detection of the SARS-CoV-2 coronavirus driving the COVID-19 human pandemic. The limitations of eDNA- or eRNA-based approaches are also summarized, and future directions and recommendations of the field are discussed. Continuous eDNA- or eRNA-based monitoring programs can potentially improve human and animal health by predicting disease outbreaks in advance, facilitating proactive rather than reactive responses.